The Impact of Terminal-Voltage Control on the Equilibrium Points and Small-Signal Stability of GFL-VSC Systems - Shun Li; Xing Yao; Cong Fu; Meng Zhan; Bo Bao (Energies)
Weak grid stability is crucial for grid-following voltage source converter (GFL-VSC) systems. Current studies primarily focus on the interaction analyses between active-power loops, whereas the influence of reactive-power loops remains unclear. To address this problem, this study focuses on terminal-voltage control (TVC) and analyzes its impact on equilibrium points (EPs) and small-signal stability by varying the TVC response speed, including three different cases: considering TVC dynamics, considering TVC rapid responses, and considering TVC slow responses. Firstly, the models of the GFL-VSC system under different scenarios are established and compared. In the EP analysis, for both TVC dynamics and TVC rapid responses, the EP of an active current remains constant and it becomes unstable in a weak grid, whereas for TVC slow responses, the EP undergoes trans-critical bifurcation; specifically, the other EP becomes stable after this bifurcation. Further, in the small-signal stability analysis, three equivalent Heffron–Phillips models based on the phase-locked loop synchronization dynamics with additional synchronization and damping coefficients are constructed and studied. By these systematical studies, the impacts of different TVC response speeds are clarified and summarized, and these analytical results are well supported by MATLAB/Simulink simulations and hardware-in-the-loop experiments.